DIAGNOSTIC ROLE OF GALECTIN-3 EXPRESSION IN BENIGN FOLLICULAR PATTERNED THYROID LESIONS, NON-INVASIVE FOLLICULAR THYROID NEOPLASM WITH PAPILLARY-LIKE NUCLEAR FEATURES (NIFTP), AND INFILTRATIVE FOLLICULAR VARIANT PAPILLARY THYROID CARCINOMA (IFVPTC) - V, Tamilselvi; Venugopal, Lakshmy; Ravikumar, Krishnan; Rajendran, Divya (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of the study was to determine the role of Galectin-3 expression in distinguishing Benign follicular patterned thyroid lesions, non- Invasive follicular thyroid neoplasm with papillary-like nuclear Features (NIFTP), and invasive follicular variant of papillary thyroid carcinoma (IFVPTC). Methods: The Institutional Human Ethics Committee reference number is 271/pathology/09/2022. A total of 85 cases were included in the study after the histopathological evaluations based on strictly defined inclusion and exclusion criteria. Study groups were created as nodular hyperplasia, follicular adenoma, follicular carcinoma, NIFTP, invasive EFVPTCs, and classical papillary thyroid carcinomas. Cytoplasmic Galectin-3 Immunohistochemistry (IHC) expression was evaluated in these cases. Galectin-3 IHC scores data were analyzed using IBM SPSS statistics. The Chi-square test was used to determine the association between the variables. p<0.05 was considered statistically significant. Results: Cytoplasmic galectin-3 IHC expression was significantly increased in malignant follicular patterned thyroid lesions compared to benign lesions with p<0.00001. Similarly, cytoplasmic galectin-3 IHC expression was significantly increased in IFVPTC when compared to NIFTP with a p-value of 0.01358. The Odds Ratio showed the positive cytoplasmic Galectin-3 expression in IFVPTC with a 7.5 times higher risk of having adverse outcome when compared to NIFTP. Conclusion: Cytoplasmic Galectin-3 IHC expression may serve as a useful biomarker in predicting the invasiveness of FVPTC and distinguishing NIFTP from infiltrative FVPTC.